Algorithm in applications - Sharma, Utpal; Bhattacharyya, Dhruba K. (Narosa Publishing House, 2010)
ALGORITHMS IN APPLICATIONS is a compilation of papers that depicts how algorithms have been applied in different problems. In the domain of computer networks and security, the book covers topics such as fast channel assignment in cellular networks, energy efficiency in wireless networks, steganography, etc. Similarly, interesting survey reports covering tuple space based mobile middleware, and peer-to-peer systems have been included. On the other hand, in the domain of machine intelligence, the book includes significant contributions on topics such as spatial data clustering, natural language parsing, grammar induction, machine learning from visual evidence, text summarization, etc. While topics such as gene-gene networking, nucleotide distribution in DNA from the domain of Bio-informatics are reported, the application of genetic algorithms in resource constrained project scheduling problem is covered in this volume. Similarly, interesting topics of algorithm design such as s-directed spanning tree, I-tree construction, multi-context in a concept lattice are also part of this volume.